Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 12 - Section 12.2 - Inverse Functions - Exercise Set: 32

Answer

$f^{-1}$(x)=$\frac{2x+3}{4}$

Work Step by Step

f(x)=$\frac{4x-3}{2}$ y=$\frac{4x-3}{2}$ x=$\frac{4y-3}{2}$ 2x=4y-3 2x+3=4y y=$\frac{2x+3}{4}$ $f^{-1}$(x)=$\frac{2x+3}{4}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.